A multi-zone spatial flow impact factor model for evaluating and layout optimization of infection risk in a Fangcang shelter hospital. (15th April 2022) - Ma, Luping; Zheng, Xiaohong; Guo, Yong; Zhong, Weide; Zhang, Yinping; Qian, Hua
Abstract: Respiratory infectious diseases have caused several pandemics and scarcity of medical resources. As a temporary hospital for infectious disease patients, the Fangcang shelter hospital requires effective air distribution. We developed the multi-zone SFIF (SFIFM ) model by combing a natural ventilation multi-zone model (MIX: Multi-zone Infiltration and eXfiltration) and spatial flow impact factor (SFIF) model, which can calculate the contribution of other zones to the risk of infection in the target zone. Compared with the experimental data in the reference, the model can be used to characterize the influence between zones. A three-zone large building was used for the analysis of the relationship between ventilation rate and SFIFM . An existed Fangcang shelter hospital was evaluated and the layout was optimized with this model. The results showed that both mechanical and natural ventilation would influence SFIFM . By optimizing the layout, the weighted SFIFM on health care worker zone could be reduced by 0.022, and the infection risk could be reduced by 14.42%. This model could more clearly show the relationship between zones, ventilation rate, concentration, and infection risk. It could be applied to evaluate and optimize the location of infectious sources, susceptibles, mechanical ventilation, and purifiers under variable conditions. This model may be helpful in reducing the risk of infection in large space buildings and providing guidance for ensuring public health safety. Highlight: The model can calculate the contribution of infection risk to the target zones. Source, susceptible, and indoor and outdoor environments are considered. The model is simple and convenient for reducing the infection risk. The layout of Fangcang shelter hospitals is evaluated. Optimizing the layout of Fangcang shelter hospitals is highly effective.